PENGARUH E-SERVICE QUALITY, CUSTOMER TRUST, DAN BRAND IMAGE TERHADAP LOYALITAS PENGGUNA MOBILE APPLICATION PROFITS ANYWHERE (Studi Pada Nasabah PT Phintraco Sekuritas Surabaya) - Adrian Fajar Eka Putra; Hartono; Yuliasnita Verlandes (Bajang Institute, 2022)
The digital era has formed a significant transformation in the company in providing the best service for its customers. Activities ranging from daily life, education, business and transactions today cannot be separated from digitalization technology. PT Phintraco Sekuritas is a securities company and a member of the Indonesia Stock Exchange and was officially established on July 1, 1999. PT Phintraco Sekuritas has a mobile application Profits Anywhere that is offered to its customers in stock transactions in the capital market with various attractive features. Therefore, it is important for PT Phintraco Sekuritas to maintain and improve e-service quliality, customer trust, and brand image to attract more customers and keep customers using the company's services continuously. The purpose of this study is to determine the effect of e-service quality, customer trust, and brand image on the loyalty of users of the Profits Anywhere mobile application to customers at PT Phintraco Sekuritas Surabaya. This study uses multiple linear regression analysis, which is assisted by data analysis software, namely IBM SPSS version 25. The sampling technique used is Non-probability Sampling with a Purposive Sampling approach. The sample used in the study was 268 respondents with certain criteria. The results of the study show that partially e-service quality has a significant influence on loyalty, customer trust partially has a significant influence on loyalty, brand image partially has a significant influence on loyalty, Then e-service quality, customer trust, and brand image simultaneously have a significant influence on the loyalty of users of the Profits Anywhere mobile application